Design of Bidirectional Same-Sense Circularly Polarized Antenna Using Metasurface - Nkimbeng, Cho Hilary Scott; Park, Ikmo (2021 15th International Congress on Artificial Materials for Novel Wave Phenomena, Metamaterials 2021, 2021)
This paper presents the design of a bidirectional same-sense circularly polarized (CP) antenna using the metasurfaces. The antenna is composed of two metasurfaces and a ground plane with etched slot sandwiched between the two substrates. Each metasurface is made up of an array of 2times 4 corner truncated patches placed back-to-back at the top and bottom of the antenna. The antenna is fed by a 50 Omega coplanar waveguide. The antenna radiates same-sense right-hand CP waves in both the front and back directions. It has overall dimensions of 48 mm times 24 mm times 3 mm (0.91lambda_{0}times 0.45lambda_{0}times 0.05lambda_{0} at 5.7 GHz). The |textStext{l}1|lt -10textdtextB impedance bandwidth is 5.21-6.26 GHz (18.4%) and a 3-dB axial ratio (AR) bandwidth is 5.36-6 GHz (11.2%) for both front and back directions. The antenna gain is 3. 0-5.29dBic for both directions within its AR bandwidth.
Keywords: Antenna gains; Axial ratio bandwidth; Circularly polarized antennas; Circularly polarized waves; Corner-truncated patch; Ground planes; Impedance bandwidths; Metasurface